Mistral no fue madre, fue lesbiana: Archivo, deseo y pedagogías disidentes. - MILLÁN BÁEZ, MICHELL (Nomadías)
This article offers a queer, feminist, and situated reading of Gabriela Mistral, challenging the patriarchal narratives that have reduced her figure and erased the dissident force of her work. Through archival approaches, performativity, and a queer ethics of care, the text highlights a Mistral who is ambiguous, affectively complex, and deeply linked to Latin American genealogies of resistance. The dialogue with Casa Particular (1990) and Paris is Burning (1990) expands this perspective by positioning Mistral alongside other marginalized bodies that build community through desire and dissidence. In this way, her work emerges as a living archive that enables new pedagogies, new memories, and new forms of accompanying those who inhabit the margins-especially in the context of the Chilean social uprising and contemporary feminist movements.